Landbrugets Gæld og en Arvegaardslovgivning. Foredrag, den 5. december 1938. - Hesselbjerg, M. (Tidsskrift for Landøkonomi, 2018)
Landbrugets Gæld og en Arvegaardslovgivning. Foredrag, den 5. december 1938.